2020
DOI: 10.3390/md18030138
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Glycolipids and a Polyunsaturated Fatty Acid Methyl Ester Isolated from the Marine Dinoflagellate Karenia mikimotoi

Abstract: A new monogalactosyldiacylglycerol (MGDG), a known monogalactosylmonoacylglycerol (MGMG) and a known polyunsaturated fatty acid methyl ester (PUFAME) were isolated from the marine dinoflagellate Karenia mikimotoi. The planar structure of the glycolipids was elucidated using mass spectroscopy (MS) and nuclear magnetic resonance (NMR) analyses and comparisons to the known glycolipid to confirm its structure. The MGDG was characterized as 3-O-β-D-galactopyranosyl-1-O-3,6,9,12,15-octadecapentaenoyl-2-O-tetradecano… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Dinoflagellates and other microalgae are a rich source of new chemistry, particularly fatty acid/polyketide-derived compounds, and 2020 was no exception. A new glycolipid 871 was isolated from a Japanese Karenia mikimotoi , 341 while amphirionin-3 872 and -6 873 and two macrolides iriomoteolide-14a 874 and -14b 875 , and one polyketide amdigenol D 876 , were isolated from a Japanese Amphidinium collections, respectively. 342–344 …”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Dinoflagellates and other microalgae are a rich source of new chemistry, particularly fatty acid/polyketide-derived compounds, and 2020 was no exception. A new glycolipid 871 was isolated from a Japanese Karenia mikimotoi , 341 while amphirionin-3 872 and -6 873 and two macrolides iriomoteolide-14a 874 and -14b 875 , and one polyketide amdigenol D 876 , were isolated from a Japanese Amphidinium collections, respectively. 342–344 …”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…By elucidation of the composition difference in molecular structures of glycolipids, we can better understand the phenotypic changes in algae and plants to explore the different functions of glycolipids associated with their structure specificities and, accordingly, possible assignments to different applications. Several galactolipids isolated from cyanobacteria, moss, and plants have been indicated in in vitro antitumor activity, ,, anti-inflammatory activity, ,, antiviral activity, , and antibacterial activity. Further, it has also been demonstrated that MGDG and DGDG have contributions to increasing loaf volumes of doughs and improving bread-making quality. ,, A galactolipid, 1,2-di- O -α-linolenoyl-3- O -β-galactopyranosyl- sn -glycerol (dLGG), isolated from jute (Corchorus capsularis L.), Citrus hystrix, spinach leaves, and Crassocephalum rabens, was determined in antitumor promotion activity in vitro . A recent study revealed that this galactolipid could inhibit 12- O -tetradecanoylphorbol-13-acetate (TPA)-induced expression of cyclooxygenase-2 (COX-2) and nitration of proteins in mouse skin .…”
Section: Fatty Acid Compositions and Bioactivities Of Mgdg And Dgdg A...mentioning
confidence: 99%
“…Several galactolipids isolated from algae, medicinal plants, and vegetables by bioassay-guided chromatographic fractionation have been determined with anti-inflammatory activity. , Rose hip (Rosa canina) had been used as a herbal remedy as a result of its anti-inflammatory property . The glycolipid in rose hips is considered to be the most critical compound with anti-inflammatory effects.…”
Section: Fatty Acid Compositions and Bioactivities Of Mgdg And Dgdg A...mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Macrophages polarize into two major functional phenotypes: classically activated type-1 macrophages (M1) with inflammatory activities, and alternatively activated type-2 macrophages (M2) with anti-inflammatory activities. 8 M2 macrophages are associated with immunomodulation, regeneration and wound healing in certain 9 situations. M1-related genes include interleukin (IL)-1β, tumor necrosis factor (TNF)-α, inducible nitric oxide synthase (iNOS) and IL6, whereas M2-related genes include mannose receptor (MR), arginase 1 (Arg1), resistin-like molecule-α/found in inflammatory zone 1 (Fizz1) and Ym1 (chitinase-like protein 3 (Chil3)).…”
Section: Introductionmentioning
confidence: 99%